APOBEC3B deletion impacts on susceptibility to acquire HIV‐1 and its advancement among individuals in western India. Issue 10 (15th August 2016) - Singh, HariOm; Marathe, Shruti D.; Nain, Sumitra; Nema, Vijay; Ghate, Manisha V.; Gangakhedkar, Raman R.
Abstract : APOBEC3B deletion polymorphism has been associated with risk of HIV‐1 acquisition and its progression. Therefore, we aimed to investigate the association of APOBEC3B ins/del polymorphism with risk of acquisition of HIV‐1 and its progression. In the present case–control study, we enrolled a total of 150 HIV‐infected individuals and 150 healthy controls. Polymorphism for APOBEC3B gene was genotyped by PCR. APOBEC3B ID, DD genotypes, and D allele were associated with higher risk of acquisition of HIV‐1 (p = 0.004, OR = 4.96; p = 0.03, OR = 3.55; and p = 0.004; OR = 1.60). The individuals with ID genotypes and combined genotype ID+DD of APOBEC3B in the presence of tobacco and alcohol showed the higher risk of advancement of HIV disease; however, risk could not reach statistical significance (OR = 1.14, 95% CI: 0.59–2.18; OR = 1.33, 95% CI: 0.83–2.15 and OR = 1.44, 95% CI: 0.77–2.69; OR = 1.50, 95% CI: 0.94–2.40). Individuals in advanced HIV disease stage and ID genotype and combined genotype ID + DD of APOBEC3B were more likely to be associated with advanced HIV disease stage but risk could not reach significant (OR = 1.50, 95% CI: 0.94–2.40; OR = 1.27, 95% CI: 0.88–1.84). Individuals with ID and DD genotype of APOBEC3B had influence on susceptibility to acquisition of HIV‐1. This suggests that APOBEC3B deletion may attenuate innate cellular immunity against HIV‐1 and thus confer the host persistence for HIV infection.